The validity of Henry VIII clauses in Australian federal legislation - Moens, Gabriel; Trone, J. (Edizioni Universita di Macerata, 2012)
The Australian High Court has stated that the federal Parliament may not abdicate its legislative powers. However, the Court’s concept of abdication only prohibits an abdication or renunciation of the power of Parliament to repeal or amend a statute. This concept of abdication is so narrow that it has not proved to be a meaningful limitation in practice. This paper argues that the Court should modify its abdication doctrine so that a delegation of power to amend statute law by regulation would constitute an abdication of legislative power. Subordinate legislation must at least be subordinate to primary legislation.